2018
DOI: 10.1021/acs.orglett.7b03790
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Controlled Selective C–S or C–C Bond Formation: Photocatalytic Sulfonylation versus Arylation of Unactivated Heterocycles Utilizing Aryl Sulfonyl Chlorides

Abstract: A visible-light-induced photocatalytic method for the arylsulfonylation of heterocycles has been developed. The synthetic utility of this reaction is reflected by the direct use of commercially available sulfonyl chlorides and heterocycles under room temperature conditions. Complementarily, the photocatalytic arylation of heterocycles by sulfonyl chlorides via extrusion of SO is feasible at elevated temperature conditions, allowing switching between arylation or arylsulfonylation with excellent chemoselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 61 publications
0
53
0
Order By: Relevance
“…Alternatively, commercially available aryl‐ and alkylsulfonly chlorides can be activated by photoredox catalysis without the need for stoichiometric amounts of an oxidant or reductant. The resulting sulfonyl radicals can be trapped with electron‐rich heterocycles to afford 134 …”
Section: Carbon–heteroatom Bond Formationmentioning
confidence: 99%
“…Alternatively, commercially available aryl‐ and alkylsulfonly chlorides can be activated by photoredox catalysis without the need for stoichiometric amounts of an oxidant or reductant. The resulting sulfonyl radicals can be trapped with electron‐rich heterocycles to afford 134 …”
Section: Carbon–heteroatom Bond Formationmentioning
confidence: 99%
“…Classical methods for the preparation of sulfones [7] include the oxidation of sulfides, [8] electrophilic aromatic sulfonylation with sulfonyl chlorides, [9] transition metal catalyzed cross coupling of arylsulfinates and aryl halides, [10][11][12] and the insertion of sulfur dioxide. [14] The sulfonyl radicals are usually in-situ generated from sulfinic acid, [15] sodium sulfinate, [16] sulfonyl chloride, [17] sulfonyl hydrazide, [18] and SO 2 [19] promoted by photo-catalysts or oxidants. [14] The sulfonyl radicals are usually in-situ generated from sulfinic acid, [15] sodium sulfinate, [16] sulfonyl chloride, [17] sulfonyl hydrazide, [18] and SO 2 [19] promoted by photo-catalysts or oxidants.…”
mentioning
confidence: 99%
“…[13] Recently, the reactions of sulfonyl radicals have received significant consideration in terms of synthetic efficiency and atom economy. [14] The sulfonyl radicals are usually in-situ generated from sulfinic acid, [15] sodium sulfinate, [16] sulfonyl chloride, [17] sulfonyl hydrazide, [18] and SO 2 [19] promoted by photo-catalysts or oxidants. Most of these methods encounter certain limitations including over-stoichiometric amounts of oxidants, harsh acid conditions, high reaction temperatures, and extra addition of metal-catalyst or photo-catalyst.…”
mentioning
confidence: 99%
“…To the best of our knowledge, the 2-sulfonylation of Nmethylpyrrole has rarely been reported, with unstable sulfur sources and complex reaction conditions oen required. 12,13 Gratifyingly, various arylsulfonyl hydrazides showed good results with N-methylpyrrole, giving the desired products 5a-i in 42-57% yields ( Table 5). We also found that when 4-methylbenzenesulnic acid was used as the sulfur source, the reaction yield (5b) signicantly improved.…”
Section: Resultsmentioning
confidence: 96%